Development of spectrum monitoring tool for Malaysia - Saman, Mohamad Afif; Ismail, Ahmad Fadzil; Badron, Khairayu; Abdul Malek, Norun Fatihah; Fakrullah, Ahmad Nasruddin 'Atiqullah (2013)
Rapid growth on new technologies and services in mobile communication leads to stronger competition in spectrum access. As a developed country, Malaysia is also affected by this trend. With the increasing numbers of subscribers, the easier solution for mobile service providers to improve the coverage area is by installing new base station (BS). Nevertheless, this increases the possibilities of interference among BS. Thus, spectrum monitoring is needed to maintain the efficiency of the network and avoid interference. However, the commercial spectrum monitoring tool is not a cost effective enough in the fast pace changing mobile communication environment. Hence, the need for development of a low cost radio frequency (RF) spectrum monitoring tool to identified and monitor interference. This paper aims to highlight the approaches taken in developing an open-source spectrum management tool for Malaysian authority. The simple low cost tool is capable to identified possible interference among BS in Global System for Mobile Communications (GSM), 2G and Universal Mobile Telecommunications System (IMT), 3G networks as well as capable to display BS cell coverage area.